Functional and evolutionary aspects of axial stability in euarchontans and other mammals. (29th November 2013) - Granatosky, Michael C.; Lemelin, Pierre; Chester, Stephen G. B.; Pampush, James D.; Schmitt, Daniel
ABSTRACT The presence of a stable thoracolumbar region, found in many arboreal mammals, is considered advantageous for bridging and cantilevering between discontinuous branches. However, no study has directly explored the link between osteological features cited as enhancing axial stability and the frequency of cantilevering and bridging behaviors in a terminal branch environment. To fill this gap, we collected metric data on costal and vertebral morphology of primate and nonprimate mammals known to cantilever and bridge frequently and those that do not. We also quantified the frequency and duration of cantilevering and bridging behaviors using experimental setups for species that have been reported to show differences in use of small branches and back anatomy (Caluromys philander, Loris tardigradus, Monodelphis domestica, and Cheirogaleus medius). Phylogenetically corrected principal component analysis reveals that taxa employing frequent bridging and cantilevering (C. philander and lorises) also exhibit reduced intervertebral and intercostal spaces, which can serve to increase thoracolumbar stability, when compared to closely related species (M. domestica and C. medius). We observed C. philander cantilevering and bridging significantly more often than M. domestica, which never cantilevered or crossed any arboreal gaps. Although no difference in the frequency of cantilevering was observed between L. tardigradus and C. medius, the duration of cantilevering bouts was significantly greater in L. tardigradus. These data suggest that osteological features promoting axial rigidity may be part of a morpho‐behavioral complex that increases stability in mammals moving and foraging in a terminal branch environment. J. Morphol. 313–327, 2014. © 2013 Wiley Periodicals, Inc.